Elimination or rescue of cells in culture by specifically targeted liposomes containing methotrexate or formyl-tetrahydrofolate. - Machy, P (1984)
Methotrexate (Mtx) inhibits cellular proliferation by blocking formyl tetrahydrofolate (THF) production. Mtx- or THF-containing liposomes were covalently coupled to Staphylococcus aureus protein A. These liposomes bound specifically in vitro to cells pre-incubated with relevant monoclonal antibodies. When liposomes contained Mtx, targeted cells died. When liposomes contained THF, targeted cells survived in the presence of quantities of Mtx in the medium sufficient to eliminate non-targeted cells. These negative or positive selection liposomes allow the recovery of either a small proportion of cells not bearing a given antigen, or a small proportion of cells bearing a given antigen, from heterogeneous cell populations.